Development of Canva-Assisted Comic Book-Based Learning Media on Ramadan Fasting Materials - Sarra, Idris; Salmilah, Salmilah; Firman, Firman; Mustakim, Risda (South Sulawesi Education Development (SSED), 2024)
This study aims to determine the results of media design, validation, practicality, and effectiveness in developing this comic-based learning media. This type of research is research and development (R&D) development, with the ADDIE development model consisting of five stages: Analysis, design, development, Implementation, and evaluation. This study's subject is a class V student of SIT Al-Hikmah Palopo. The instruments used were material and media expert validation sheets, student practicality questionnaires, and student pretest and posttest questionnaires to determine the effectiveness of products in improving student learning outcomes. The data analysis techniques used are qualitative and quantitative descriptive data. The results of the development of comic-based learning media. The result of canvas-assisted comic-based media design is producing learning media in printed products. The media and material validation results met the validity requirements of 82.50% with the category of very valid. The results of the practicality test conducted by teachers and students met the practicality requirements, which were 85.27% and in the category of very practical. The effectiveness of comic-based learning media results are seen from the pretest and posttest scores, where students obtained an average N-gain score of 57.7% in the